Strategi Kepala Sekolah dalam Mewujudkan Religious Culture di SMK Darussalam Blokagung Tegalsari Banyuwangi Tahun Pembelajaran 2018/2019 - Hadiono, Abdi Fauji; Khaudli, Moh. Imam; Hilmia, Farida (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2019)
The objectives set in this study are: (1) To find out how the principal's strategy in realizing religious culture in SMK Darussalam Blokagung Tegalsari Banyuwangi 2018/2019 academic year; (2) to find out how the efforts made by school principals in realizing religious culture in SMK Darussalam Blokagung TegalsariBanyuwangi 2018/2019 academic year; (3) to find out the supporting and inhibiting factors of school principals in realizing religious culture in SMK Darussalam Blokagung Tegalsari Banyuwangi in the 2018/2019 academic year; This study uses descriptive qualitative, data analysis using SWOT analysis and data validity techniques using triangulation. The results of his research are that The principal's strategy in realizing religious culture in SMK Darussalam Blokagung includes: (1) Educators and education personnel prioritize pesantren graduates. (2) assisting in the reading of the names of students by educators and education staff. (3) diniyah activities for students who are not at the boarding school and are held once every 3 days with a duration of 60 minutes. (4) There is a need for advice on realizing religious culture by disciplining activities through journals or reports on each individual